2012
DOI: 10.1002/poc.2971
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of substituted aspirins with amino acids

Abstract: Acyl transfers are key reactions in biology and in the laboratory. In biological systems they are involved in energy transport, in the assembly of complex molecules and in the mechanisms of efficient action of many hydrolytic enzymes. We report a mechanistic and calculational study of the selective N‐acylation reactions of amino acids by substituted aspirins, under mild conditions, in water at 25 °C. The acetylated amino‐acid products of the reactions were identified by nuclear magnetic resonance, and the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Although intramolecular catalysis is efficient and frequently observed in enzyme catalysis and in biomimetic models which include the reactions of amides and carboxylic and phosphate esters, it is less explored in synthetic preparations. In this regard, it has been shown that N ‐acetylaminoacids can be conveniently prepared using aspirin as the acetylating agent of amino acids in aqueous medium . Here, we demonstrate that the related 3‐acetoxy‐2‐naphthoic acid (3Ac) can be employed in the selective acetylation of primary amines in ethanol.…”
Section: Introductionmentioning
confidence: 92%
“…Although intramolecular catalysis is efficient and frequently observed in enzyme catalysis and in biomimetic models which include the reactions of amides and carboxylic and phosphate esters, it is less explored in synthetic preparations. In this regard, it has been shown that N ‐acetylaminoacids can be conveniently prepared using aspirin as the acetylating agent of amino acids in aqueous medium . Here, we demonstrate that the related 3‐acetoxy‐2‐naphthoic acid (3Ac) can be employed in the selective acetylation of primary amines in ethanol.…”
Section: Introductionmentioning
confidence: 92%